Morval, M., Cyr, F., Palardy-Laurier, Y., & Rubin-Porret, J. (1986). Stress et famille: vulnérabilité, adaptation. - Tessier, Ph.D., Réjean (Canadian Journal of Counselling and Psychotherapy, 2011)
n/a